2019
DOI: 10.1016/j.corsci.2019.108194
|View full text |Cite
|
Sign up to set email alerts
|

Role of irradiation and irradiation defects on the oxidation first stages of a 316L austenitic stainless steel

Abstract: The role of irradiation and irradiation defects on the oxidation first stages of 316 L alloy was investigated. A sample with both a proton pre-irradiated and an unirradiated area was exposed to a simulated PWR environment during 24 hours. Irradiation defects and Radiation Induced Segregation at grain boundary and on irradiation defects were characterized and quantified and their effect on the oxidation was evaluated. Irradiation affects the morphology, thickness and chemistry of the oxide layers formed. It enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The displacement per atom (dpa) induced by the beam is quite small, about 0.04 dpa, based on the Stopping and Range of Ions in Matter (SRIM) analysis 45 . In 316L SS, a proton irradiation dose of 1-1.5 dpa is considered close to the saturation of the dislocation loops and the radiation induced segregations phenomenon, where effects on post-corrosion rate can be observed 46 . In this study, the damage is about 25 times less than that.…”
Section: Radionuclide Productionmentioning
confidence: 99%
“…The displacement per atom (dpa) induced by the beam is quite small, about 0.04 dpa, based on the Stopping and Range of Ions in Matter (SRIM) analysis 45 . In 316L SS, a proton irradiation dose of 1-1.5 dpa is considered close to the saturation of the dislocation loops and the radiation induced segregations phenomenon, where effects on post-corrosion rate can be observed 46 . In this study, the damage is about 25 times less than that.…”
Section: Radionuclide Productionmentioning
confidence: 99%
“…For a comprehensive understanding of the composition and structure of the oxide formed on the metal surface, as well as the depth of the inner oxide layer following irradiation, extensive studies have been conducted, which have been summarized in Table 6 [19-21, 76, 82, 83]. Although Deng et al [20] have already reported that a finer oxide grain in the inner oxide film was formed on a 3-dpa proton-irradiated 316 L austenitic stainless steel after exposure to the primary water of the simulated PWR for 500 h, it is generally accepted that irradiation does not alter the crystal structure and the qualitative chemistry of the inner and outer oxides formed on materials, which can be characterized using high-resolution TEM (HRTEM) [19,21,74,77,78,82,84,85]. Similar to the unirradiated sample, the oxide layer maintains its characteristic double-layer structure when stainless steel is irradiated.…”
Section: Effect Of Irradiation Defects On Corrosionmentioning
confidence: 99%
“…Both layers have been characterized as spinel structures. In addition, Ni enrichment at the oxide/ matrix interface has been observed [19,82]. However, based on the available study data [19-21, 74, 76, 82, 85-89], it has been observed that irradiation affects the quantitative chemistry, morphology, and thickness of the oxide layers formed on the alloys.…”
Section: Effect Of Irradiation Defects On Corrosionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors observed RIS on different types of sinks, i.e. grain boundaries [4,[7][8][9][10][11], dislocation loops [10][11][12][13][14] and lines [11,15] and cavities [8,13,14]. (S)TEM and APT are extensively used to study microstructural features induced by radiation damage because of their complementarity: accurate crystallography information for TEM and accurate composition measurements for APT.…”
Section: Introductionmentioning
confidence: 99%